From Liberal to Conservative: Effects on False Memories and Response Bias by Emotion and EMDR in DRM Paradigm - Janiszewska,Agata (2014)
Eye Movement Desensitization Reprocessing (EMDR) has been investigated recently in false memories and specifically in the DRM paradigm. EMDR has been shown to decrease emotionality of the problematic memories in PTSD, but also to decrease false memories. No studies have to date shown how emotion and memory is effected by EMDR in the DRM paradigm when non-emotional wordlists are coupled with a negative encoding context. The 48 Swedish-speaking participants were between 18-62 years of age. Words from the Swedish DRM lists (Johansson & Stenberg, 2002) were encoded during an emotional slideshow, the pictures were chosen from the IAPS (Lang, Bradley, & Cuthbert, 2008). After either eye movements condition a recognition test followed. Each participant completed two blocks; negative and neutral. With mixed model ANOVAs, two significant findings were found. The negative condition led to significantly fewer false memories than the neutral condition in the no eye movement group, replicating previous studies. A significant interaction was also found between emotion and eye movement on response bias. T-tests revealed that the neutral condition had a response bias that was more conservative than the negative in the group with no eye movements. However, in the eye movement group, the response bias in the neutral condition was more liberal and the negative more conservative. This study extends previous research on emotion in the DRM paradigm (ex. Pesta, Murphy & Sanders, 2001), by using a negative encoding context instead of negative content.
Keywords: EMDR; horizontal eye movements; DRM; Emotion; Memory; False Memories